Thai ethnomedicinal plants as resistant modifying agents for combating Acinetobacter baumannii infections - Phatthalung Pinanong; Chusri Sasitorn; Voravuthikunchai Supayang P (BMC Complementary and Alternative Medicine, 2012)
Abstracts Background Acinetobacter baumannii is well-recognized as an important nosocomial pathogen, however, due to their intrinsic resistance to several antibiotics, treatment options are limited. Synergistic effects between antibiotics and medicinal plants, particularly their active components, have intensively been studied as alternative approaches. Methods Fifty-one ethanol extracts obtained from 44 different selected medicinal plant species were tested for resistance modifying agents (RMAs) of novobiocin against A. baumannii using growth inhibition assay. Results At 250 μg/ml, Holarrhena antidysenterica, Punica granatum, Quisqualis indica, Terminalia bellirica, Terminalia chebula, and Terminalia sp. that possessed low intrinsic antibacterial activity significantly enhanced the activity of novobiocin at 1 μg/ml (1/8xminimum inhibitory concentration) against this pathogen. Holarrhena antidysenterica at 7.8 μg/ml demonstrated remarkable resistant modifying ability against A. baumannii in combination with novobiocin. The phytochemical study revealed that constituents of this medicinal plant contain alkaloids, condensed tannins, and triterpenoids. Conclusion The use of Holarrhena antidysenterica in combination with novobiocin provides an effective alternative treatment for multidrug resistant A. baumannii infections.